Protocol of Spinal Deformity Surgery and Anaesthesia in Children and Adult: Recommended Preoperative and Perioperative Diagnostic and Treatment Algorithm in Spinal Deformity Surgery - Šalaševičius, Lukas; Savičienė, Nijolė; Alsytė, Rasa; Gasiūnaitė, Diana; Bernotavičius, Giedrius; Lapteva, Ona; Saniukas, Kęstutis; Vaitkevičius, Arūnas; Kvaščevičius, Robertas; Daugelavičius, Vidūnas; Šipylaitė, Jūratė; Ročka, Saulius (Lietuvos chirurgija, 2021)
Spinal deformity surgery is one of the most challenging surgeries that is only performed by highly professional multidisciplinary team in dedicated spinal centres. In the paper, the authors share and present the algorithm for safe and successful management of complex spinal disorders in Vilnius University Hospital Santaros Clinics.
Keywords: spinal deformities; adult; children; algorithm; surgery; anesthesia